The Role of Social Media in Raising Environmental Awareness among Millennials - Efendi, Septiyano; Sunjaya, Heldy; Kurniawan, Sandi (CONVERSE Journal Communication Science, 2025)
Environmental awareness has become a critical issue among millennials as global environmental degradation increases. As a primary communication platform for this generation, social media holds significant potential to raise awareness and drive behavioral changes toward environmental issues. This study aims to analyze social media's role in enhancing millennials' environmental awareness. The research adopts a literature review method by analyzing various recent and relevant scholarly journals and literature. Findings reveal that social media functions as a dissemination and participatory medium, enabling millennials to engage in environmental campaigns actively. In conclusion, social media significantly fosters awareness and mobilizes collective actions on environmental issues. However, its effectiveness is influenced by content quality and users’ digital literacy. This study recommends strengthening communication strategies through social media to maximize its impact on environmental awareness.